Development of an Imtaq Project-Based Program to Enhance Early Childhood Faith and Piety - Sauqy, Dzulfikar; Susilawati, Ulfah; Pratiwi, Indy Ari (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
The suboptimal implementation of religious and moral values in early childhood learning has created a gap between curriculum planning and classroom practice. This study aims to develop an